Ankylosis of Temporomandibular Joints - S. S. Sethi; J. L. Gupta; J. L. Shrivastava (Indian Journal of Plastic Surgery)
A technique of osteotomy through the ramus of the mandible has been described in cases where the ramus forms a bony block with the skull bones. Clear acrylic pulley is inserted between the bony ends to produce the false joint. Post operative excercises are stressed upon to maintain the joint function. The maximum follow up at present is two years.